COVID 19: PERBEDAAN KINERJA KEUANGAN PERUSAHAAN FARMASI DAN JASA DI INDONESIA - Sugeng Riadi; Resti Nur Karimah (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The Covid-19 pandemic has exerted its influence on various sectors of the Indonesian economy, leading to diverse consequences. This study aims to elucidate the contrasting financial impacts experienced by pharmaceutical and service companies before and during the Covid-19 era. The study includes a population consisting of pharmaceutical and service companies listed on the Indonesian Stock Exchange during the periods of 2018-2019 and 2020-2021. The sample size comprises 9 pharmaceutical companies and 25 service companies. The analytical approach involves the use of the Paired Sample T-test and the Wilcoxon signed-rank test. The findings of this investigation reveal a nuanced scenario. Among pharmaceutical companies, the analysis indicates a lack of significant differences in key financial metrics, specifically the Current Ratio, Debt to Equity Ratio, Return on Equity, and Earnings per Share. In contrast, within the service sector, the situation presents a divergent picture. Significant differences are observed in terms of the Current Ratio, Debt to Equity Ratio, Return on Equity Ratio, and Earnings per Share.